2014
DOI: 10.3171/2014.7.jns132691
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for unruptured arteriovenous malformations of the brain is better than conservative management for selected cases: a prospective cohort study

Abstract: Object The aim of this study was to identify patients who are likely to benefit from surgery for unruptured brain arteriovenous malformations (ubAVMs). Methods The authors' database was interrogated for the risk and outcome of hemorrhage after referral and the outcome from surgery. Furthermore, the outcome from surgery incorporated those cases excluded from surgery because of perceived greater risk (sensitivity analysis). Finally, a comparison was made for the authors' patients between the natural history and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
61
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 35 publications
7
61
1
1
Order By: Relevance
“…1 Both SIVMS and ARUBA cohorts had predominantly nonsurgical interventions and bAVM obliteration rates of 63% to 71% were observed in SIVMS. 16 In contrast, Bervini et al 35 presented a 25-year microsurgical series from Sydney, Australia, of 427 unruptured bAVMs patients, who were stratified according to the Spetzler-Ponce class 4 : for class A (n=190), the rate of permanent neurological deficit with mRS increase >1 was 1.6% (95% confidence interval, 0.3-4.8%); class B (n=107), 14.0% (95% confidence interval, 8.6-22.0%); and class C (n=44), 38.6% (95% confidence interval, 25.7-53.4%). 35,36 Subsequent sensitivity analyses on the same database by Korja et al 37 showed no statistical difference to the combined classes A and B adverse outcome rate of 7.7% when nonoperated patients were assumed to have adverse outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…1 Both SIVMS and ARUBA cohorts had predominantly nonsurgical interventions and bAVM obliteration rates of 63% to 71% were observed in SIVMS. 16 In contrast, Bervini et al 35 presented a 25-year microsurgical series from Sydney, Australia, of 427 unruptured bAVMs patients, who were stratified according to the Spetzler-Ponce class 4 : for class A (n=190), the rate of permanent neurological deficit with mRS increase >1 was 1.6% (95% confidence interval, 0.3-4.8%); class B (n=107), 14.0% (95% confidence interval, 8.6-22.0%); and class C (n=44), 38.6% (95% confidence interval, 25.7-53.4%). 35,36 Subsequent sensitivity analyses on the same database by Korja et al 37 showed no statistical difference to the combined classes A and B adverse outcome rate of 7.7% when nonoperated patients were assumed to have adverse outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…The recent work of Bervini and colleagues, Nerva and colleagues, as well as the report in the current issue provide sufficient substance to recommend microsurgery to patients with unruptured AVM Spetzler-Martin grade 1 and 2 (corresponding to Spetzler-Ponce class A) [3,11,14,16]. In contrast, treatment of unruptured Spetzler-Martin grade 3 and 4 AVMs needs to be seen critically.…”
mentioning
confidence: 81%
“…[2][3][4]10,11,20,[22][23][24]31,36,43 A related concern was the aggregation of the various treatment modalities that perhaps preferably should have been tested separately. 2,5,10,11,13,18,20,[23][24][25]33,43,46,53 The approach adopted by ARUBA's designers was that the variety of patients and treatment choices were a fact of life, to be accepted as such. 29 Heterogeneity can provide in ductive strength to pragmatic trial results.…”
Section: Concerns Regarding the Heterogeneity Of Patients And The Gromentioning
confidence: 99%